Primera cita de los jumiles comestibles Edessa bifida y Edessa championi (Hemiptera: Pentatomidae) y su importancia en la cultura entomofágica en la comunidad rural de “El Zompantle”, Taxco de Alarcón, Guerrero, México - Silva-García, Francisca; Figueroa-Castro, Pedro; López-Martínez, Victor; Pérez-Villalba, Elba (Instituto de Ecología, A.C., 2018)
In the present scientific note we report for the first time two edible bugs: Edessa championi (Distant 1881) and Edessa bifida (Say 1832) (Hemiptera: Pentadomidae) in the rural community “El Zompantle”, municipality of Taxco de Alarcón, Guerrero. Also we performed a short study of their importance in the entomophagy culture of families of this community.